A METHOD FOR CORRECTING BIAS IN SPONTANEOUS POTENTIAL (SP) LOG READING DUE TO HEAVY PRESENCE OF METALLIC MINERALS - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2005)
In reservoir characterization and modeling, information derived from well log surveys (Figure 1) plays an important role. Petrophysical properties such as porosity and water saturation are important factors in the determination of hydrocarbon accumulation. (The same is true for the determination of reservoir geometrical dimensions.) Inaccurate Spontaneous Potential (SP) log derived shale contents (V) results in inaccurate porosity and water saturation. SP log is catagorized as lithology log, which primary role is to differentiate between permeable zones and non- permeable zones (i.e. shale). SP log also has secondary purposes such as determination of shale contents and formation water resistivity, as well as its use in many reservoir geological analyses. Some problems that are often asscociated with geological complexity in Indonesia is that many subsurface formations contains significant amount of minerals that have the potential to bias log survey reading including SP log's. Considering SP log's wide span of presence, misleading SP log reading may also have adverse consequence at wider scale. Therefore, a measure is required to minimize the SP log's potential bias due to presence of metallic minerals. The method presented in this paper is suggested to be used for the purpose.